Teaching of clinical pharmacy to pharmacists at the faculty of postgraduate education using the opportunities of distance education - Bilai, I. M.; Mykhailiuk, Ye. O.; Bilai, A. I.; Dariy, V. I.; Білай, Іван Михайлович; Михайлюк, Євгеній Олегович; Білай, Андрій Іванович; Дарій, Володимир Іванович (London : Cognum Publishing House, 2021)
Abstract. The main task of the organization of professionally-oriented education are the methodological support of the educational process and the practical activities of future pharmacists. The main areas of study related to the introduction of the newest information and educational technologies in the educational process during quarantine. Combining methodological support and digital forms of education, we create the informational educational object of the department in which separate structural components are distinguished: texts of information, test tasks, presentations of lectures, which are implemented by the computer. Improving the quality of postgraduate education should enhance the qualifications of specialists, given that the pharmacist learns in the process of professional activity.
Keywords: postgraduate education; pharmacy; distance learning